Probationary services in a pandemic. Results from an empirical study in Austria - Stempkowski, Monika (Probation journal, 2021)
In March 2020 the first lockdown due to COVID-19 was imposed in Austria, forcing NEUSTART, the organisation providing probationary services, to adapt the way of interacting with their clients. An online survey was conducted examining how these changes affected the everyday work of the probation officers. Results indicated that they managed to stay in contact with their clients, although difficulties could be observed concerning specific groups. Further questions concerned areas such as domestic violence, strains due to the restrictions experienced as well as coping strategies used by the clients. Concerning the well-being of the probation officers, differences were found between residents of urban and rural areas respectively as well as between people living with or without children. The lack of personal contact with clients and colleagues proved to be the most important source of discomfort, while at the same time working from home entailed certain advantages.